Proteomic Analysis of Vesicle-Producing Pseudomonas aeruginosa PAO1 Exposed to X-Ray Irradiation - Zhang, Li; Zhao, Shi-qiao; Zhang, Jie; Sun, Ying; Xie, Ya-liu; Liu, Yan-bin; Ma, Cui-cui; Jiang, Bo-guang; Liao, Xue-yuan; Li, Wen-fang; Cheng, Xing-jun; Wang, Zhen-ling (Frontiers in Microbiology, 2020)
Ionizing irradiation kills pathogens by destroying nucleic acids without protein structure destruction. However, how pathogens respond to irradiation stress has not yet been fully elucidated. Here, we observed that Pseudomonas aeruginosa PAO1 could release nucleic acids into the extracellular environment under X-ray irradiation. Using scanning electron microscopy (SEM) and transmission electron microscopy (TEM), X-ray irradiation was observed to induce outer membrane vesicle (OMV) formation in P. aeruginosa PAO1. The size distribution of the OMVs of the irradiated PAO1 was similar to that of the OMVs of the non-irradiated PAO1 according to nanoparticle tracking analysis (NTA). The pyocin-related proteins are involved in OMV production in P. aeruginosa PAO1 under X-ray irradiation conditions, and that this is regulated by the key SOS gene recA. The OMV production was significantly impaired in the irradiated PAO1 lys mutant, suggesting that Lys endolysin is associated with OMV production in P. aeruginosa PAO1 upon irradiation stress. Meanwhile, no significant difference in OMV production was observed between PAO1 lacking the pqsR, lasR, or rhlR genes and the parent strain, demonstrating that the irradiation-induced OMV biosynthesis of P. aeruginosa was independent of the Pseudomonas quinolone signal (PQS).